Case Study On Use Area Parking At New Market City Shopping Center Bogor - Syaiful Syaiful; Yena Elvira (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
New Market City Shopping Bogor is a research object to the availability of parking areas. Perception assessment of park users to park a distance of 42.86% with a distance of> 200 m, the distance is very great influence in determining the parking area. Difficulty entering the parking structure also affects the level of parking services at 39.52%. Level of difficulty occurs because the road to the parking lot filled with public transportation that stops in the place.